RETRACTED: Interrogating Western Perspective on Islam and Terrorism - Budiwiranto, Bambang; Alfiah, Alfiah (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
This article has been retracted: please see Kalam Policy on Article Withdrawal (https://ejournal.radenintan.ac.id/index.php/KALAM/about/editorialPolicies#custom-6).This article has been retracted at the request of the Author. The author has published the content of this article in JICSA (Journal of Islamic Civilization in Southeast Asia) Vol. 2 No. 2 (2013) entitled: Terrorism: Between Islamic Radicalism and Misinterpretation of Jihad Doctrine. (https://journal.uin-alauddin.ac.id/index.php/jicsa/article/view/768).Apologies are extended to journal readers as this was not detected during the submission process.